Identification of cholesterol binding sites in the serotonin(1A) receptor - Sengupta, Durba; Chattopadhyay, Amitabha (Journal of Physical Chemistry B, 2012)
The serotonin(1A) receptor is a representative member of the G protein-coupled receptor (GPCR) superfamily and serves as an important drug target in the development of therapeutic agents for neuropsychiatric disorders. Previous work has shown the requirement of membrane cholesterol in the organization, dynamics, and function of the serotonin(1A) receptor. We show here that membrane cholesterol binds preferentially to certain sites on the serotonin(1A) receptor by performing multiple, long time scale MARTINI coarse-grain molecular dynamics simulations. Interestingly, our results identify the highly conserved cholesterol recognition/interaction amino acid consensus (CRAC) motif on transmembrane helix V as one of the sites with high cholesterol occupancy, thereby confirming its role as a putative cholesterol binding motif. These results represent the first direct evidence for membrane cholesterol binding to specific sites on the serotonin(1A) receptor and represent an important step in our overall understanding of GPCR function in health and disease.

In vitro and in silico studies on membrane interactions of diverse Capsicum annuum flower gamma-thionin peptides - Nikte, Siddhanta; Gahankari, Apurva; Mulla, Javed; Sengupta, Durba; Joshi, Manali; Tamhane, Vaijayanti (Proteins-Structure Function and Bioinformatics, 2019)
Thionins are small, cysteine-rich peptides that play an important role in plant defense, primarily through their interactions with membranes. Eight novel gamma-thionin peptides (CanThio1-8) were isolated from the flower of Capsicum annuum. Sequence analysis revealed that the peptides cluster into three groups. A representative peptide from each group (CanThio1, 2, and 3) was used for experimental characterization. Interestingly, peptides were found to possess some cytotoxic activity against normal human embryonic kidney cell line but higher cytotoxicity against cancer cell line MCF-7. CanThio3 peptide was chosen as a representative peptide to study the molecular mechanism of action on membranes. Microsecond timescale atomistic simulations of CanThio3 were performed in the presence of a POPC (1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine) lipid bilayer. Simulations revealed that CanThio3 interacts with the bilayer and causes lipid thinning in the vicinity. Nonpolar amino acids specific to the alpha-core region of CanThio3 along with nonpolar residues in the gamma-core region are seen to interact with the lipid tails. The differences in the amino acid sequence of CanThio peptides in these regions explain the variability in cytotoxic activities. In summary, our results demonstrate the membrane-mediated activity of a novel series of gamma-thionin peptides from C. annuum.
Keywords: Capsicum annuum; Cytotoxicity; gamma-thionin; MD simulations; Membrane

Interplay between membrane curvature and cholesterol: role of palmitoylated caveolin-1 - Krishna, Anjali; Sengupta, Durba (Biophysical Journal, 2019)
Caveolin-1 (cav-1) is an important player in cell signaling and endocytosis that has been shown to colocalize with cholesterol-rich membrane domains. Experimental studies with varying cav-1 constructs have suggested that it can induce both cholesterol clustering and membrane curvature. Here, we probe the molecular origin of membrane curvature and cholesterol clustering by cav-1 by using coarse-grain molecular dynamics simulations. We have performed a series of simulations of a functionally important cav-1 construct, comprising the membrane-interacting domains and a C-terminal palmitoyl tail. Our results suggest that cav-1 is able to induce cholesterol clustering in the membrane leaflet to which it is bound as well as the opposing leaflet. A positive membrane curvature is observed upon cav-1 binding in cholesterol-containing bilayers. Interestingly, we observe an interplay between cholesterol clustering and membrane curvature such that cav-1 is able to induce higher membrane curvature in cholesterol-rich membranes. The role of the cav-1 palmitoyl tail is less clear and appears to increase the membrane contacts. Further, we address the importance of the secondary structure of cav-1 domains and show that it could play an important role in membrane curvature and cholesterol clustering. Our work is an important step toward a molecular picture of caveolae and vesicular endocytosis.

Investigation of the captopril-insulin interaction by mass spectrometry and computational approaches reveals that captopril induces structural changes in insulin - Ghosh, Amrita; Pawar, Aiswarya B.; Chirmade, Tejas; Jathar, Swaraj M.; Bhambure, Rahul; Sengupta, Durba; Giri, Ashok P.; Kulkarni, Mahesh J. (ACS Omega, 2022)
ABSTRACT: Post-translational modifications remarkably regulate proteins' biological function. Small molecules such as reactive thiols, metabolites, and drugs may covalently modify the proteins and cause structural changes. This study reports the covalent modification and noncovalent interaction of insulin and captopril, an FDA-approved antihypertensive drug, through mass spectrometric and computation-based approaches. Mass spectrometric analysis shows that captopril modifies intact insulin, reduces it into its ``A'' and ``B'' chains, and covalently modifies them by forming adducts. Since captopril has a reactive thiol group, it might reduce the insulin dimer or modify it by reacting with cysteine residues. This was proven with dithiothreitol treatment, which reduced the abundance of captopril adducts of insulin A and B chains and intact Insulin. Liquid chromatography tandem mass spectrometric analysis identified the modification of a total of four cysteine residues, two in each of the A and B chains of insulin. These modifications were identified to be Cys6 and Cys7 of the A chain and Cys7 and Cys19 of the B chain. Mass spectrometric analysis indicated that captopril may simultaneously modify the cysteine residues of intact insulin or its subunits A and B chains. Biophysical studies involving light scattering and thioflavin T assay suggested that the binding of captopril to the protein leads to the formation of aggregates. Docking and molecular dynamics studies provided insights into the noncovalent interactions and associated structural changes in insulin. This work is a maiden attempt to understand the detailed molecular interactions between captopril and insulin. These findings suggest that further investigations are required to understand the long-term effect of drugs like captopril.

Improved protein dynamics and hydration in the martini3 coarse-grain model - Kharche, Shalmali; Yadav, Manjul; Hande, Vrushali; Prakash, Shikha; Sengupta, Durba (Journal of Chemical Information and Modelling, 2024)
The Martini coarse-grain force-field has emerged as an important framework to probe cellular processes at experimentally relevant time- and length-scales. However, the recently developed version, the Martini3 force-field with the implemented Go model (Martini3Go), as well as previous variants of the Martini model have not been benchmarked and rigorously tested for globular proteins. In this study, we consider three globular proteins, ubiquitin, lysozyme, and cofilin, and compare protein dynamics and hydration with observables from experiments and all-atom simulations. We show that the Martini3Go model is able to accurately model the structural and dynamic features of small globular proteins. Overall, the structural integrity of the proteins is maintained, as validated by contact maps, radii of gyration (Rg), and SAXS profiles. The chemical shifts predicted from the ensemble sampled in the simulations are consistent with the experimental data. Further, a good match is observed in the protein-water interaction energetics, and the hydration levels of the residues are similar to atomistic simulations. However, the protein-water interaction dynamics is not accurately represented and appears to depend on the protein structural complexity, residue specificity, and water dynamics. Our work is a step toward testing and assessing the Martini3Go model and provides insights into future efforts to refine Martini models with improved solvation effects and better correspondence to the underlying all-atom systems.

Increased cholesterol interactions in the active conformational state of the glucagon-like peptide-1 receptor - Naglekar, Amit; Chattopadhyay, Amitabha; Sengupta, Durba (Biophysical Journal, 2026)
The glucagon-like peptide-1 receptor (GLP-1R) is a class B G-protein-coupled receptor that plays an important role in metabolic regulation and consequently is a target for type 2 diabetes and obesity therapeutics. Although cholesterol has been reported to be implicated in receptor activation, its interactions with the receptor during the activation cycle have not been probed. Using coarse-grained molecular dynamics simulations, we have characterized the cholesterol interactions with GLP-1R in four conformational states: the inactive, partially active, GLP-1-bound active, and exenatide-bound active conformational states. We observed that the cholesterol hotspots vary between the receptor states with an increased enrichment of cholesterol around the receptor in the active conformational states. Importantly, more favorable interaction energetics and increased residence times of cholesterol were identified in the active conformational state of the receptor, although lower in magnitude than previously reported. Notably, subtle differences could be distinguished between the GLP-1-bound and exenatide-bound receptor, underlining the ligand-specific effects. Our findings emphasize the increased selectivity of cholesterol toward the active state of GLP-1R and highlight the role of conformational dynamics in receptor-lipid interplay. Our work helps to understand how cholesterol modulates GLP-1R, with potential effects on its role as a regulator in lipid metabolism, thereby opening avenues to leverage these lipid interactions in targeted drug therapy. SIGNIFICANCE This study provides an understanding of how cholesterol directly influences the function of GLP-1R, a key therapeutic target for metabolic diseases including type 2 diabetes and obesity. Using coarse-grained molecular dynamics simulations, we show that cholesterol binding, favorable interactions, and residence times increase when GLP-1R is in its active states. These interactions vary subtly depending on the activating ligand, highlighting ligand-specific effects. Our findings highlight the critical role of conformational dynamics in receptor-lipid interplay and suggest that understanding these cholesterol-GLP-1R interactions could pave the way for novel strategies in targeted drug therapy for metabolic disorders.